2011
DOI: 10.1186/1471-2288-11-77
|View full text |Cite
|
Sign up to set email alerts
|

Logistic random effects regression models: a comparison of statistical packages for binary and ordinal outcomes

Abstract: BackgroundLogistic random effects models are a popular tool to analyze multilevel also called hierarchical data with a binary or ordinal outcome. Here, we aim to compare different statistical software implementations of these models.MethodsWe used individual patient data from 8509 patients in 231 centers with moderate and severe Traumatic Brain Injury (TBI) enrolled in eight Randomized Controlled Trials (RCTs) and three observational studies. We fitted logistic random effects regression models with the 5-point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 26 publications
0
102
1
Order By: Relevance
“…The p values determining the significance of the fixed‐effect terms were calculated using the likelihood ratio test. Analyses were implemented using R (version 3.0.1, see http://www.r-project.org) 18, 19.…”
Section: Methodsmentioning
confidence: 99%
“…The p values determining the significance of the fixed‐effect terms were calculated using the likelihood ratio test. Analyses were implemented using R (version 3.0.1, see http://www.r-project.org) 18, 19.…”
Section: Methodsmentioning
confidence: 99%
“…The first level concerns the individual characteristic of children, and the second level is represented by the socioeconomic characteristic and overweight's risk factors for parents (level-household). Assuming that the probability to be overweight or obese may be statistically dependent on both the variance of individual characteristics (level 1) and the parent's characteristics (level 2), we considered a multilevel logistic regression analysis based on a logit link function and a function of binomial distribution [35]- [38]. Statistical analyses were performed using SAS Software 9.2, and all results were weighted with an effect relative to the sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Although the LME4, MCMCglmm, and PROC GLIMMIX packages were described for estimation in various binary GLMM models (Kim, Choi, & Emery, 2013;Li, Lingsma, Steyerberg, & Lesaffre, 2011;Zhang et al, 2011), the performance of the ORDINAL package has not yet been reported for binary outcomes nor for the calculation of agreement measures. Our focus in this paper is to explore the use of these four aforementioned packages in R and SAS to calculate the measures of agreement for multiple raters classifying test results using a binary scale.…”
Section: Methodsmentioning
confidence: 99%